Self-generated active sites in graphene oxide-like materials by controlling the oxidative decomposition reactions of Sargassum. Issue 6 (December 2021) - Pareja-Rodríguez, Raúl; Freile-Pelegrín, Yolanda; Robledo, Daniel; Ruiz-Gómez, Miguel; Martínez-Flores, Rocio; Rodríguez-Gattorno, Geonel
Abstract: Graphene and its derivates are at the center of an ever-growing research effort due to their exceptional properties; however, their applications remain limited due to high production costs. Obtaining carbonaceous bidimensional materials from biomass is now intensively studied; neverthelees, most methodologies are based on controlled atmosphere (N2 ) and high temperatures. In this report, it was explored the obtaining of graphene oxide-like material from Sargassum species (here identified as GOS) by a thermal decomposition at relatively low temperature (420 °C) and without the atmosphere control. The 2D character of the products depends not only on temperature and atmosphere but also on the part of Sargassum species (leaves, vesicles, or axis). Because of the oxidative decomposition reactions and impurities, GOS exhibits self-functionalization with active sites that play a crucial role in the mechanism of Pb 2+ adsorption (74.5–745 mg L −1 ) in an aqueous solution. The removal capacity is remarkably better than those reported for materials that are specifically designed in more complex processes such as activation and/or chemical doping. The proposed strategy is envisaged as a bridge between small and large-scale graphene oxide-like materials production from biomass. Graphical Abstract: ga1 Highlights: A low-temperature method for obtaining graphene oxide-like material from Sargassum (GOS). Structural organization of GOS depends on the seaweed section. The DSC study indicates that Sargassum sp. presented the lowest energy consumption. The "self-doped" impurities in GOS allow high chemical activity at the interface for ions as Pb 2+ .